Development of Web-Based Animal Adoption Application (Case Study: Medan Animal Rescue) - Gohzali, Hernawati; Khory, Dario; Linardi, Winnie Quinn; Veronica, Kherin; Halim, Arwin (Bahasa Indonesia, 2023)
Animals that receive welfare are in good condition, both physically and mentally. Based on research conducted by Bracke's Animal Protection Index (API), Indonesia received a 'D' rating. The explosion of the street animal population has become an issue in urban areas. The lack of care and handling of street animals has led to an explosion in the population of street animals such as stray cats and dogs. This population explosion has also led to various problems such as the rise of animal abuse cases, and the illegal capture of street animals for meat sale. Medan Animal Rescue is an organization engaged in rescuing abandoned animals and distributing abandoned animals as pets. In carrying out its operational activities, Medan Animal Rescue still uses simple and conventional methods. To overcome the problem of not maximizing the operational activities that take place, the utilization of information technology in the form of web-based animal adoption applications is very important to be applied to Medan Animal Rescue. The results obtained from the development of a web-based animal adoption application at Medan Animal Rescue show that the average user acceptance of the application is 85.54%. This means that the application is very helpful and worth using for animal welfare.